2012
DOI: 10.1002/jhm.1917
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: Multidisciplinary fall prevention strategies in the acute care inpatient population

Abstract: BACKGROUND:Inpatient falls are common adverse events that lead to inpatient injury, increased length of stay, healthcare costs, litigation, and are a focus of patient safety and healthcare quality. Fall prevention methods are currently evolving to address the problem.PURPOSE:To examine the available data evaluating multidisciplinary fall prevention strategies in the acute inpatient setting.DATA SOURCES:A complete literature search of MEDLINE, CINAHL, EMBASE and the Cochrane Library through December 2011 was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…The rate of falls showed an almost two-fold difference between the hospitals with the lowest and highest rates. Previous studies indicated that the rates of falls in acute care hospitals varied between the hospitals, ranging from 2 to 10 per 1,000 patient-days (DiBardino, Cohen, & Didwania, 2012). The difference in the rate of falls among the four hospitals might again be due to the differences in patient background, fall prevention program performed in the hospitals, and underreporting bias of the falls.…”
Section: Discussionmentioning
confidence: 93%
“…The rate of falls showed an almost two-fold difference between the hospitals with the lowest and highest rates. Previous studies indicated that the rates of falls in acute care hospitals varied between the hospitals, ranging from 2 to 10 per 1,000 patient-days (DiBardino, Cohen, & Didwania, 2012). The difference in the rate of falls among the four hospitals might again be due to the differences in patient background, fall prevention program performed in the hospitals, and underreporting bias of the falls.…”
Section: Discussionmentioning
confidence: 93%
“…[2][3][4] It is a limitation of studies using administrative databases that important information, such as practice management strategies, is often lacking. The lack of association between PNB and in-patients falls in our study may very well relate to systems issues and perhaps selection bias: those hospitals that have had previous problems with falls or lack training in the safe use of PNB may be less likely to use PNB for arthroplasty patients; and those hospitals that use PNBs regularly for arthroplasty may have systems in place to make them work while keeping patients safe, including multidisciplinary fall prevention programs.…”
Section: In Replymentioning
confidence: 99%
“…Finally, an additional metaanalysis including 4 randomized, controlled trials and one retrospective cohort study, Johnson et al calculated an odds ratio of 3.9 (p < 0.01) of falling for subjects with a continuous femoral or posterior lumbar plexus block of greater than 12 h (incidence = 2.2%) compared with subjects with either no block, a single-injection block, or a perineural infusion of less than 12 h (incidence = 0.5%). 4 To my knowledge, there are no data contradicting these findings when single-injection and continuous PNBs are differentiated.…”
mentioning
confidence: 90%
“…High rates of poly-pharmacology have been reported in psychiatric hospitals [38]. Medication with strongest links to an increased risk of falling includes serotonin reuptake inhibitors and tricyclic antidepressants [39], antipsychotic agents [40], benzodiazepines and anticonvulsants [25].…”
Section: Medicationmentioning
confidence: 99%